2017
DOI: 10.1016/j.apmr.2017.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Robot-Based Assessments of Upper Extremity Function

Abstract: Objective To examine the validity of 5 robot-based assessments of arm motor function post-stroke. Design Cross sectional. Setting Outpatient clinical research center. Participants Volunteer sample of 40 participants, age >18 years, 3–6 months post-stroke, with arm motor deficits that had plateaued. Intervention None. Main Outcome Measures Clinical standards included the Fugl-Meyer Arm Motor Scale (FMA), and 5 secondary motor outcomes: hand/wrist subsection of the FMA; Action Research Arm Test (ART); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In addition to this, we would also be determining the maximum distance covered in left and right directions by the metacarpophalangeal sensor and it will be termed as maximum left and right displacement, respectively. Peak velocity: It is the overall maximal value of the velocity profile between movement onset and end (McKenzie et al., 2017). Moreover, average velocity will be calculated separately for each movement phase (Hussain et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this, we would also be determining the maximum distance covered in left and right directions by the metacarpophalangeal sensor and it will be termed as maximum left and right displacement, respectively. Peak velocity: It is the overall maximal value of the velocity profile between movement onset and end (McKenzie et al., 2017). Moreover, average velocity will be calculated separately for each movement phase (Hussain et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Colombo et al [ 23 25 ] further demonstrated a moderate correlation between robot-based kinematic parameters and FMA-UE scores; work by Zollo et al [ 26 ], Otaka et al [ 27 ], Duret et al [ 28 , 29 ], and Pila et al [ 30 ] made comparable observations. Other authors achieved similar results by collecting kinematic data during the performance of tasks consisting of drawing geometric figures of different shapes [ 31 , 32 ], tracing large semicircular arcs to measure UE active range of motion [ 33 ], or deriving kinematic parameters from distal movements (e.g., wrist and finger movements) [ 34 ]. Larger correlations were shown by Krebs et al [ 35 ] when implementing more complex analytical models than those utilized in previous work.…”
Section: Introductionmentioning
confidence: 96%
“…Robotic technologies are emerging as a new approach for neurological assessment. They offer advantages over existing clinical tools as they can provide objective and precise measures of many sensory, motor and cognitive behaviours [18][19][20]. In recent years, there have been several new tasks developed using robotic technology for evaluating different aspects of proprioception including position sense [10,[20][21][22][23][24][25][26][27], sense of effort [28] and kinesthesia [29].…”
Section: Introductionmentioning
confidence: 99%